FAILURES OF LOCAL SCHOOL BOARDS IN PERFORMING THEIR ROLES AS SOCIETY’S REPRESENTATIVE IN CONTROLLING PUBLIC SCHOOLS IN WAITING FOR SUPERMAN FILM - Amalia, Farizza Noor (LANTERN (Journal on English Language, Culture and Literature), 2013)
United States of America, which is recognized as a powerful country puts a great concern toward education. This can be seen from the way government provides free public education for its citizens. Yet, the quality is questionable. The Board of Education is the council responsible for providing good education; it is also responding to community wishes for educational betterment. In its leadership, problems appear and lead to failing public schools. This eventually brings failures to students. Such existing situation in American public schools can be seen through literary works, film is one in case. Waiting for Superman is one showing it.